Uveitis in spondyloarthropathies: Current concepts - Krati Chauhan (Indian Journal of Rheumatology)
Uveitis is the inflammation of the middle layer of the eye, the Uvea. Spondyloarthropathies are systemic disorders with common clinical and pathological features. Uveitis is an important and frequent extraarticular manifestation of spondyloarthropathies. Recently, there has been a remarkable enhancement in the management of uveitis with the approval of biologics. This review discusses epidemiology, clinical features and management of uveitis associated with spondyloarthropathies.